UPAYA GURU AL-QUR’AN HADIST DALAM MENINGKATKAN MINAT BELAJAR SISWA MELALUI PENERAPAN MEDIA PEMBELAJARAN LED INTERAKTIF SMART TV PADA SISWA KELAS X A MAN INSAN CENDEKIA SAMBAS TAHUN AJARAN 2022/2023 - Al-Adiat Putra Praja; Arnadi Arnadi; Eliyah (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study is to reveal about the efforts of Al-Qur'an Hadith teachers to increase students' interest in learning through the application of Interactive LED Smart TV learning media. This research has three research objectives including the following; First, to find out the plan of the Al-Qur'an Hadith teacher to increase students' interest in learning through the application of interactive LED smart TV media for students in class. The results of this research are: 1) Planning for the Al- Qur'an Hadith teacher in improving learning media through the application of Smart TV Interactive LED learning media, namely in the following way: a) Preparing the Syllabus b) Preparing the Learning Implementation Plan c) Preparing the learning media. 2) Implementation of Al-Qur'an Hadith teachers in improving learning media through the application of Smart TV Interactive LED learning media, starting from preliminary, core to closing activities. 3) Evaluation of Al- Qur'an Hadith teachers in increasing interest in learning through Smar TV Interactive LED learning media, namely through formative and summative evaluations.